2006
DOI: 10.1104/pp.105.076497
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Aluminum Interactions in Soybean in Relation to Aluminum Tolerance. Exudation of Specific Organic Acids from Different Regions of the Intact Root System

Abstract: (J.S., L.V.K.) Aluminum (Al) toxicity and phosphorus (P) deficiency often coexist in acid soils that severely limit crop growth and production, including soybean (Glycine max). Understanding the physiological mechanisms relating to plant Al and P interactions should help facilitate the development of more Al-tolerant and/or P-efficient crops. In this study, both homogeneous and heterogeneous nutrient solution experiments were conducted to study the effects of Al and P interactions on soybean root growth and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
165
1
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(187 citation statements)
references
References 41 publications
9
165
1
12
Order By: Relevance
“…Under conditions of low phosphorous availability in the soil, strains and soybean cultivars which are suitable for and efficient in the use of this nutrient, show better productive performance. Obtaining these efficient genotypes will be possible with a better understanding of the physiological and genetic bases for phosphorus use efficiency (PUE) (LIAO et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of low phosphorous availability in the soil, strains and soybean cultivars which are suitable for and efficient in the use of this nutrient, show better productive performance. Obtaining these efficient genotypes will be possible with a better understanding of the physiological and genetic bases for phosphorus use efficiency (PUE) (LIAO et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As interações Al-P que ocorrem nas células, entretanto, são ainda pouco conhecidas e, infelizmente, pouco se tem feito (LIAO et al, 2006). O metabolismo do P é extremamente complexo envolvendo dezenas de moléculas e rotas metabólicas, em diferentes compartimentos celulares.…”
Section: Introductionunclassified
“…Studies with soybean (Liao et al, 2006), rice (Nakagawa et al, 2003) and maize (Gaume et al, 2001) suggested that P addition could alleviate Al toxicity. According to , P-dependent alleviation of Al toxicity is based on two possible mechanisms.…”
Section: Effect Of Aluminum On Citrusmentioning
confidence: 99%
“…Al can be precipitated directly with P on the root surface, in root cell walls or within root cells or in the soil solution (Silva et al, 2001;Nakagawa et al, 2003;Zheng et al, 2005). As the other possible mechanism, external application of P could alleviate Al toxicity indirectly through improving the root morphology, which facilitates nutrient uptake or by secreting special root exudates (Liao et al, 2006).…”
Section: Effect Of Aluminum On Citrusmentioning
confidence: 99%